2015
DOI: 10.1016/j.eats.2014.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Excision of Acetabular Osteoid Osteoma: Computer Tomography–Guided Approach

Abstract: Osteoid osteoma is a benign osteoblastic tumor that occurs in the subcortical shaft and metaphysis of the long bones of the lower extremities; however, intra-articular lesions are also possible. Intra-articular osteoid osteomas are rare, and clinical symptoms are often less specific and, thereby, may lead to misdiagnosis. The definitive treatment for osteoid osteoma is the excision of the nidus. We present the case of a 23-year-old man with a 4-year history of right anterior hip pain, subsequently diagnosed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
(24 reference statements)
0
12
1
Order By: Relevance
“…Previous reports have described successful treatment of OO by an arthroscopic approach. 8,14 These publications, however, reported on intra-or juxta-articular lesions, not an acetabular rimebased lesion, which is presented in our study. Taman et al 8 reported on transarticular arthroscopic removal of a juxta-articular lesion using CT guidance.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Previous reports have described successful treatment of OO by an arthroscopic approach. 8,14 These publications, however, reported on intra-or juxta-articular lesions, not an acetabular rimebased lesion, which is presented in our study. Taman et al 8 reported on transarticular arthroscopic removal of a juxta-articular lesion using CT guidance.…”
Section: Discussioncontrasting
confidence: 50%
“…6 Hip arthroscopy is an alternative treatment option for some of these lesions and provides direct visual confirmation of excision. [7][8][9] In addition, periarticular structures are identified through the arthroscope and can be carefully protected throughout the course of the procedure. Arthroscopy may be an ideal solution for patients who have concomitant symptomatic femoroacetabular impingement (FAI) and associated labral-chondral dysfunction that can be addressed concurrently with OO excision or curettage.…”
mentioning
confidence: 99%
“…OOs around the acetabulum can often border the cortical bone-subchondral interface, making ablation challenging. Three technique case reports 7 , 8 , 9 used arthroscopic-assisted radiofrequency ablation of lesions; however, what differentiates the technique used in our case is the preservation of the acetabular cartilage and subsequent filling of the lesion with bone graft substitute.…”
Section: Discussionmentioning
confidence: 91%
“…The majority of tumors in the pelvis are malignant while in the proximal femur majority of the tumors are benign 15 . Osteoid osteoma and bone cysts can be treated by arthroscopy assisted surgery 16,17 . Chondral Structure Pathologies: Almost all of the chondral, capsular, ligamentous and synovial pathologies can be addressed arthroscopically so exact decision of treatment can be done after identifying the pathology by arthroscopy (Figure 8).…”
Section: Avascular Necrosis (Avn)mentioning
confidence: 99%